Public interest and its supremacy: a study on the principle of the supremacy of public interest over private interest (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This article has two objectives. On one hand, it intends to investigate the elements that integrate the concept of “public interest” and, mainly, those that do not integrate it. On the other hand, after examining the possible legal content of the “public interest” and the beacons for its configuration, this essay will present reasons against the existence and functionality of a “principle of the supremacy of public interest over the private interest”, especially in relation to its use as a basis for legitimizing administrative actions that restrict individual rights of individuals - especially taxpayers.
Keywords: administrative law; tax law; public interest; principle of the supremacy of public interest over the private interest; public interest and parameters of control; control of public administration